HUBUNGAN METAKOGNITIF DAN MOTIVASI BELAJAR DENGAN INTEGRITAS AKADEMIK PADA MAHASISWA PREKLINIK DI FAKULTAS KEDOKTERAN UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA TAHUN 2020 - Destiana Putri Nurfauziah (2021)
Academic integrity is a major part of academic culture in the sense of being obedient to basic principles, including academic honesty, mutual trust, mutual openness, mutual respect, and a sense of responsibility. However, there are few data on understanding of academic integrity among medical students. It is expected that the performance of student academic integrity can further improve the behaviour of student academic integrity. Student performance can be improved through metacognitive and learning motivation. To determine the correlation between metacognitive and learning motivation with the academic integrity among preclinical medical students. This study used proportional stratified sampling, sample size were 156 medical students of batch 2nd, 3th, 4th, data were collected from adaptation of metacognitive activities inventory, academic motivation scale, and academic integrity. The research design used was the cross sectional method. Data analysis in this study used the Chi-square test. The research design used was the cross sectional method. Data analysis in this study used the Chi-square test. The results of the statistical test, there was no correlation between metacognitive and academic integrity(p=0.365) and learning motivation with integrity (p=0.77). There was no correlation between metacognitive and learning motivation with academic integrity of preclinical medical students. External factor are farther can improve the academic integrity of the student.